2011
DOI: 10.1016/j.eurpolymj.2010.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of a coarse grained model for an athermal all-polystyrene nanocomposite system

Abstract: Abstract:The structure of a polystyrene matrix filled with tightly cross-linked polystyrene nanoparticles, forming an athermal nanocomposite system, is investigated by means of a Monte Carlo sampling formalism. The polymer chains are represented as random walks and the system is described through a coarse grained Hamiltonian. This approach is related to self-consistent-field theory but does not invoke a saddle point approximation and is suitable for treating large three-dimensional systems. The local structure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
82
1
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 47 publications
12
82
1
5
Order By: Relevance
“…We provide here some details on the FOMC model, which was introduced in ref 41. The configurational partition function on which the Monte Carlo sampling is based is expressed as a functional integral over the paths of all chains and as an integral over all nanoparticle positions and orientations.…”
Section: Model and Simulation Methodology Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…We provide here some details on the FOMC model, which was introduced in ref 41. The configurational partition function on which the Monte Carlo sampling is based is expressed as a functional integral over the paths of all chains and as an integral over all nanoparticle positions and orientations.…”
Section: Model and Simulation Methodology Modelmentioning
confidence: 99%
“…The summation extends over all free and grafted segments of the system, excluding only the interaction between the segments which are directly connected to a particle and the particle itself. The interaction of a polymeric segment and a nanoparticle can be calculated using eqs 11-13 of ref 41, which are restated in the Supporting Information to the present paper, with suitable Hamaker constants for the polymer and the particle. The Hamaker constant governing the interaction between two spherical bodies can be calculated as 45 …”
Section: Model and Simulation Methodology Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of NPs can change the dynamics of polymers and therefore shifts the glass transition temperature [14] and slows down the diffusion of polymer chains [15]. Recently, the dynamics of polymer melts and concentrated polymer solutions have been studied intensively by experiments [16,17], theory and computer simulations [18][19][20][21]. It was found that the properties of polymers would be influenced by many parameters, such as size, shape, and concentration of NPs and interaction strength between polymer and NP [10].…”
Section: Introductionmentioning
confidence: 99%